A ANPEd, a pós-graduação, a pesquisa e a veiculação da produção intelectual na área da educação - Alceu Ravanello Ferraro (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
Taking the period from 1989 to 1993 when the author was president of the executive committee of the National Association of Postgraduate Studies and Research in Education ANPEd, this article begins by examining the conditions in which postgraduate studies in education emerged (the beginning of 70s) and the creation of the National Association (1978), as well as focusing on the nature of the association and the challenges faced by it during its first eleven years of existence. It then analyses the policy of prioritising the scientific statute of the association which covered a series of initiatives related to the working groups, the format of the annualm meetings, the Scientific Committee, the relationship with the Brazilian Society for the Progress of Science, the creation of the Forum of Postgraduate Programmes in Education and the research Evaluation and Perspectives for the Field of Education: 1982-1991. Finally, focusing attention on the following years, it emphasises initiatives like the creation of the Brazilian Review of Education, the new dynamics of the regional research meetings and the great advance, both quantitative and qualitative, with relation to the production and dissemination of knowledge in the field. The article concludes externalising the conviction that, despite disagreeing on important points, the successive directorates of ANPEd knew how to discern, preserve and improve initiatives, which were to become permanent collective conquests.